Legislative dynamics of mitigation and adaptation framework policies in the EU - Fleig, Andreas; Schmidt, Nicole; Tosun, Jale (European policy analysis, 2017)
In this study we examine the adoption of climate framework laws in 20 member states of the European Union (EU) from 1990 until 2015. Our analysis is guided by the following research questions: First, which EU member states have adopted climate change legislation that addresses mitigation, adaptation, or both? Second, do EU countries act coherently or do we observe differences across countries regarding the response strategy or point in time of policies directed towards climate change? Third, comparing mitigation and adaptation frameworks, which approach came first and did it affect the adoption of the respective other? Our findings show that all countries save one (i.e., Hungary) covered in the analysis have adopted framework laws tackling mitigation and/or adaptation to climate change. While we did not observe a coherent pattern with respect to timing or sequence of adaptation and mitigation frameworks, we found that the best predictor of a national government's behavior is the behavior of the governments of other countries. However, the response of EU member states to climate change is less homogenous than one would have expected based on previous literature. In addition, by highlighting that mitigation and adaptation measures are equally prominent, at least within our sample of EU countries, we complement current climate change literature that often places mitigation efforts at the forefront in terms of legislation activity. Future research should examine this issue more closely, as this dynamic is likely to continue since the Paris Agreement gave prominence to adaptation.